Lepidostomatidae G Ulmer 1903 - Küçükbasmaci, İbrahým; Canbulat, Savaş (Zenodo, 2020)
Published as part of Küçükbasmaci, İbrahým & Canbulat, Savaş, 2020, A List of the Caddisflies (Insecta: Trichoptera) from Kyrgyzstan, with a New Record (Triaenodes reuteri McLachlan 1880), pp. 113-122 in Zootaxa 4896 (1) on page 115, DOI: 10.11646/zootaxa.4896.1.6, http://zenodo.org/record/4359410

Family Lepidostomatidae Lepidostoma nigrescens (Mey & Jung 1989) —Range: China, Kazakhstan, and Kyrgyzstan (Huang et al. 2005; Mey & Jung 1989; Morse 2020; Yang, et al. 2016). Lepidostoma posdnjakovi (Mey 1986) —Range: Kyrgyzstan (Mey 1986; Morse 2020).
Keywords: Insecta; Arthropoda; Trichoptera; Animalia; Biodiversity; Lepidostomatidae; Taxonomy